1975
DOI: 10.1001/archneur.1975.00490510033001
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoleukodystrophy

Abstract: Adrenoleukodystrophy was diagnosed pathologically in 17 male patients. The diagnosis was suggested by clinical and laboratory signs of primary adrenal failure and by neurological signs referable to the degeneration of white matter. Neurological findings usually predominated over clinical stigmata of adrenal failure. Adrenal biopsy has proved to be the most reliable diagnostic test, while brain biopsy has often been misleading. The histological picture of the brain lesion differs substantially from that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Cytoplasmic trilamellar structures, presumed morphologic evidence of lipid accumulation, have been observed in brain, peripheral nerves, testes, and adrenal cortex (1,3,5). Recent studies have demonstrated that these tissues (6)(7)(8) and skin fibroblasts (9,10) cultured from patients having either disease accumulate long-chain saturated fatty acids, especially hexacosanoic acid (C26:0).…”
Section: Introductionmentioning
confidence: 99%
“…Cytoplasmic trilamellar structures, presumed morphologic evidence of lipid accumulation, have been observed in brain, peripheral nerves, testes, and adrenal cortex (1,3,5). Recent studies have demonstrated that these tissues (6)(7)(8) and skin fibroblasts (9,10) cultured from patients having either disease accumulate long-chain saturated fatty acids, especially hexacosanoic acid (C26:0).…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal ALD, clinical symptoms are present at birth and an autosomal recessive mode of inheritance is followed (4). This differs from the better known childhood form of ALD, an X-linked recessive disorder, in which symptoms appear after 3-5 years of normal development (2). The cytoplasmic lipid inclusions observed in these disorders were shown to be cholesterol esterified to very long chain fatty acids (VLCFA) (5); both disorders are characterized biochemically by increased levels of VLCFA in both plasma and cultured skin fibroblasts (6).…”
mentioning
confidence: 95%
“…The term adrenoleukodystrophy (ALD) refers to a group of degenerative neurological disorders characterized by demyelination and by cytoplasmic lipid inclusions in the central nervous system, adrenal cortical cells, and Schwann cells (1)(2)(3). Several forms of the disorder have been described.…”
mentioning
confidence: 99%
“…The lack of peroxisomes would also explain the increased blood level of bile acid precursors (7,8) and possibly of pipecolic acid (9), assuming it reflects a deficiency in glutaryl-CoA oxidation (10). Adrenoleukodystrophy constitutes another hereditary disorder in which the accumulation of very longchain fatty acids (11) and also myelin degeneration (12,13) apparently reflect a peroxisomal defect. As new findings increase the scope of the possible peroxisomal involvement in metabolic inherited disorders, their participation is being considered for hyperpipecolatemia (8,14), glutaric aciduria (10), dicarboxylic aciduria (15,16), hyperoxaluria (14,17), glycinuria (17), testicular feminization (18), and cerebrotendinous xanthomatosis (8,14).…”
mentioning
confidence: 99%